ஓப்பீட்டு நோக்கில் கணக்கதிகாரமும் ஆஸ்தான கோலாகலமும் / A Comparative Study of Kanakkathigaram and Asthanakolaakalam - முனைவர் இரா. தனசுபா / Dr. R. Dhanasuba (International Journal of Tamil Language and Literary Studies, 2022)
Mathematics is a branch of science that interacts with human life. Mathematics is also an essential part of everyone's life, both educated and uneducated. Mathematics might have appeared at the same time as the human race started. Ancient Tamil literature speaks of the mathematical knowledge of the Tamils. The mathematical Tamil texts available to us show that our forefathers wrote many mathematical books in Tamil and were also geniuses in the field of mathematics. Many texts were distorted and destroyed by the passage of time. The rest of the mathematical traces have been printed by some mathematicians. Among the books that have been published are ‘Kanakathikaram’ and ‘Asthana Kolagalam’. Both texts are studied limitedly and are a vital subject to comparative scrutiny. Hence, this article ponders over a comparative study on the selected Tamil Mathematical treatises.